Comparison of shear wave elastography with gray‐scale USG and CT for quantitative evaluation of rectus femoris muscle. Issue 4 (29th January 2023) - Yi, Jisook; Cha, Jang Gyu; Hahn, Seok
Abstract: Purpose: The purpose of this study was to compare the measurement of shear wave elastography (SWE) and gray scale ultrasonography (GSU) and CT attenuation of mid‐rectus femoris (RF) muscle in healthy adults. Methods: This prospective study included 70 participants with a healthy body mass index (<25 kg/m 2 ) between June 2019 and January 2020. Echo intensity (EI) grading of RF on GSU was performed. SWE was performed for the three levels of the RF. Measurements were repeated 10 min after the first measurement. The mid‐RF attenuation on CT was also measured. Interobserver agreement of EI grade among three readers was assessed using weighted‐kappa statistics. The reliability of SWE was assessed using intraclass correlation coefficient. The correlations between the SWE and CT/GSU measurements were analyzed. Results: Interobserver agreement of EI grade on GSU by the three radiologists was moderate to substantial ( k  = 0.562–0.767). The inter‐session agreements for SWE were almost perfect for mid RF ( k  = 0.822–0.829) and substantial for proximal and distal RF ( k  = 0.767–0.795). There were significant correlations between SWE‐EI and SWE‐CT attenuation ( p  < 0.001, respectively) at the mid‐RF. Conclusions: SWE measurements on mid‐RF demonstrated the highest reliability. SWE parameters showed a strong correlation with EI on GSU and attenuation on CT. Abstract : We evaluated the SWE measurement of mid RF muscle in healthy subjects. The SWE measurement were significantly correlated with GSU visual grade and CT attenuation of mid RF muscle.